Recurrence of superficial vein thrombosis in patients with varicose veins. (August 2016) - Karathanos, Christos; Spanos, Konstantinos; Saleptsis, Vassileios; Tsezou, Aspasia; Kyriakou, Despina; Giannoukas, Athanasios D
Objective: To investigate which factors other than history of superficial vein thrombosis (SVT) are associated with recurrent spontaneous SVT episodes in patients with varicose veins (VVs). Materials and methods: Patients with a history of spontaneous SVT and VVs were followed up for a mean period of 55 months. Demographics, comorbidities, and thrombophilia screening test were analyzed. Patients were grouped according to the clinical–etiology–anatomy–pathophysiology classification. A multiple logistic regression analysis with the forward likelihood ratio method was undertaken. Results: Thirteen patients out of 97 had a recurrence SVT episode during the follow-up period. All those patients were identified to have a thrombophilia defect. Protein C and S, antithrombin, and plasminogen deficiencies were more frequently present in patients without recurrence. Gene mutations were present in 38% in the nonrecurrence group and 77% in the recurrence group. After logistic regression analysis, patients with dislipidemia and mutation in prothrombin G20210A (FII) had an increased risk for recurrence by 5.4-fold and 4.6-fold, respectively. No deep vein thrombosis or pulmonary embolism occurred. Conclusions: Dislipidemia and gene mutations of F II are associated with SVT recurrence in patients with VVs. A selection of patients may benefit from anticoagulation in the short term and from VVs intervention in the long term.